MODIFICATION OF RISK ANALYSIS AND ACTION CONTROL OF THE HAZARD EVENT BY FMEA-SAW METHODS WITH DELPHI METHODS IN APPLICATION OF DRINKING WATER SAFETY PLAN (RPAM) IN PDAM KOTA PEKALONGAN - Reperiza Furqon, Muhammad
The research about risk management in PDAM study location in PDAM Pekalongan, Pekalongan City, Central Java. The Water Safety Plan (WSP-Operator) in PDAM Pekalongan City begin with : (1) intake or raw water storages, (2) water treatment units and (3) water distribution units which is piping system that deliver the treated water procduct in form of dringking water to the use or society. Hazard event in dringking water quality that may occurs in PDAM Pelaongan City analized by conductiong laboratorium test of drinking water quality through sampling in supply chain, water treatmnent plant, and household connection that can be used as basis in developing FMEA Methodolgy. Development of FMEA Method done by aligning indicators and sub indocatos of severity which is happened in PDAM Pekalongan City related to 4K (Quality, Quantity, Continuity, Affrodability) by adding Dephi Method. Failure Mode and Effect Analysis (FMEA) method which has been developed can be describe the characteristics of severity, probability level of occurance, detection level and authority level that produce Risk Priority Number (RPN) which will develop in two phase that is peak hours and regular hours in water usage of PDAM Pekalongan City. Risk priority of hazard event listed alternatively for control measure by using Simple Additive Weighting (SAW) method. By having these FMEA-SAW method can be concluded a comperhesive risk of hazard event and control measure combining with the laboratorium result test of water quality by means of given the best control measure alternatives as recommendations to PDAM Pekalongan City in planning of prevention and mitigations action for hazard event in an attempt of sustainable water safety plan.